2017
DOI: 10.1177/0739456x17707811
|View full text |Cite
|
Sign up to set email alerts
|

When and How Much Did the Green Line LRT Increase Single-Family Housing Values in St. Paul, Minnesota?

Abstract: Studies quantifying value added of transit often cannot differentiate whether the premiums are transit effects or location effects. Limited studies have examined the timing of value added. Using before and after data, this study explores the impact of the Green Line LRT on housing sales prices. Compared to the studied period before its funding announcement, its announcement increased housing values by $9.2/sq ft and its commencement increased sales prices by $13.7/sq ft. Further analyses show that housing valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
(52 reference statements)
0
24
0
Order By: Relevance
“…Ignoring the presence of spatial autocorrelation would lead to biased and inconsistent parameter estimates. The traditional, plain linear regression that cannot tackle spatial effects (e.g., spatial autocorrelation and spatial heterogeneity) is not as acceptable as it used to be in spatial data modeling [49][50][51][52][53].…”
Section: Methodsmentioning
confidence: 99%
“…Ignoring the presence of spatial autocorrelation would lead to biased and inconsistent parameter estimates. The traditional, plain linear regression that cannot tackle spatial effects (e.g., spatial autocorrelation and spatial heterogeneity) is not as acceptable as it used to be in spatial data modeling [49][50][51][52][53].…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, there is solid empirical evidence that rail transit can lead to dynamic real estate development (Guthrie and Fan 2013), although this relationship has taken two decades to be fully acknowledged and accepted. Since 2010, studies have increasingly focused on TODs as market responses to transit development, especially on capitalization of transit proximity through land and housing premiums, and modeled and quantified such effects (Cao and Lou 2018;Duncan 2011aDuncan , 2011bGolub, Guhathakurta, and Sollapuram 2012;Higgins and Kanaroglou 2016;Mathur and Ferrell 2009;Park, Huang, and Newman 2016;Zhang et al 2018). Most studies use hedonic price models (see literature review on this topic by Bartholomew and Ewing 2011) with substantial efforts to control for negative externalities such as neighborhood opposition and air pollution, and to account for self-selection.…”
Section: Three "Ds" As Normative Frameworkmentioning
confidence: 99%
“…Cervero and Duncan (2002) reported that being near commuter rail stations added commercial land values in a Californian county, and the value of land in the business district and other districts within 0.25 mile of a station was 23% and 120% higher, respectively. Cao and Lou (2018) confirmed that rail accessibility has a positive relationship with singlefamily house prices in St. Paul, the United States. Using a dataset of single-family houses transacted from 2000 to 2018, Zhang et al (2016) quantitatively evaluated the house price effect of urban rail transit using a dataset of 35 cities in China and determined that house prices increase by 2.33% for every 100% increase in rail transit mileage.…”
Section: Transit and House Pricesmentioning
confidence: 68%